Analysis of topic trends on the relationship between corporate reputation and reporting quality using bibliometric - Sari, Rafika; Safdar, Muhammad (Realible Accounting Journal, 2026)
This study aims to examine the emerging research directions, contemporary issues, and thematic developments in the relationship between corporate reputation and the quality of corporate reporting A bibliometric analysis combined with a Systematic Literature Review and network visualization was conducted on 109 articles published between 1990 and 2024 retrieved from the Scopus database. The results show that 11 out of 13 empirical studies reported a positive influence of corporate reputation on reporting quality, while 2 articles indicated that reputable firms may strategically limit disclosure transparency. This suggests a growing scholarly interest in the topic but also reflects a significant research gap. the study highlights the need to incorporate legitimacy theory, stakeholder theory, agency theory, and signaling theory to deepen understanding of the mechanisms linking reputation and reporting quality.